Excess Pore Pressure Migration Analysis Due to High Embankment Construction – Case Study East Kalimantan - Lie, Edwin; Rahardjo, Paulus Pramono; Wijaya, Martin (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2024)
A 42-inch pipeline traverses a predominantly flat right-of-way (ROW), running from south to north in East Kalimantan. Adjacent to the ROW, a coal mine concession was located on the western side, while the Mahakam River lies a further 3 km to the east. A mining waste dump has been constructed since 2010, situated in an area underlain by soft alluvium soil (Qa). The waste was stacked, reaching heights of up to 75 meters, with its toe approximately 200 m from the edge of the ROW. In 2016, a failure occurred in the ROW, causing the 42-inch pipeline to shift a maximum of 6.8 m horizontally, and rise by 2.0 m within a 300 m span. A geotechnical investigation was then conducted, consisting of 7 CPTu with dissipation testing. The CPTu results indicated high pore pressure, with a layer of soft clay ranging from 15 to 32 m thickness found in the ROW area. A hypothesis was formulated suggesting that the soft clay was not fully consolidated. Hence, the failure of the pipeline was possibly caused by the migration of excess pore water pressure accumulated during the construction of the waste dump. Results of the investigation indicated that the permeability coefficient was 2.5 times greater in the horizontal direction compared to the vertical ones (kh/kv = 2.5), allowing the pore water pressure to migrate more easily in the horizontal direction. This study aims to elucidate how the migration of excess pore water pressure in the horizontal direction influences ground stability. The analysis was conducted using finite element software MIDAS GTS NX, with the kh/kv varying from 2.5 to 100 times to explore excess pore pressure movement behaviors. The results of this study confirm that excess pore pressure migration can occur horizontally if the horizontal permeability coefficient is larger than its vertical counterpart. Thus, this study highlights that the greater the permeability coefficient and the larger the ratio, the further the excess pore pressure travels. Moreover, the horizontal displacement increases with the permeability coefficient ratio.